Effects of State-Level Funding Systems on Identification Rates of Students with Autism Spectrum Disorders - Michelle Powers; Brad Uhing (The Advocate, 2023)
Identification rates of children with autism spectrum disorders (ASD) have been increasing since the year 2000, while federal special education funding has remained stagnant. Researchers gathered data from states related to individual state funding systems, per pupil spending and identification rates of students with ASD to determine if state spending or special education funding methods affected identification rates of students with ASD. While specific funding methodology did not predict rates of identification or PPS, a correlational analysis of individual state PPS and ASD identification rates did have significant results. Spending amounts per pupil corresponded to rates of identification for ASD.
Keywords: Autism; funding systems; IDEA